The Branch Library of Medicine MuÌˆnster created a tablet toolbox for embedding mobile digital learning resources into the curriculum - Obst, Oliver (Journal of EAHIL, 2016)
The Branch Library of Medicine of the University of MuÌˆnster recently finished the ipad lending project easyphysikum, where 250 undergraduates got an iPad Air for loan equipped with every learning ressource to pass the preclinical exams. The project showed, that a digital mobile learning infrastructure represent an added value compared to traditional ways of learning. In May 2015 the library escalated the project to make it available to all students of medicine.